Prehospital emergency medicine for children receiving palliative home care in Germany—a cross-sectional, exploratory study of EMS providers - Hauch, Holger; El Mohaui, Naual; Vaillant, Vera; Sander, Michael; Kriwy, Peter; Rohde, Marius; Wolff, Johannes; Berthold, Daniel; Schneck, Emmanuel (Frontiers in Pediatrics, 2023)
Background: The prevalence of children with life-limiting conditions is rising, and since the amendment of the social insurance code in Germany, palliative home care teams have treated an increasing number of children. These teams provide 24/7 readiness, yet some parents still call the general emergency medical service (EMS) for various reasons, exposing EMS providers to complex medical problems in rare diseases. Questions arose about the experiences of EMS providers and whether they felt prepared for emergencies involving children treated by a palliative care team. Methods: This study used a mixed methods approach to focus on the interface between palliative care and EMS. First, open interviews were conducted, and a questionnaire was developed based on the results. The variables included demographic items and individual experiences with patients. Second, a case report of a child with respiratory insufficiency was presented to assess the spontaneous treatment intentions of EMS providers. Finally, the need, relevant topics, and duration of specific training in palliative care for EMS providers were evaluated. Results: In total, 1,005 EMS providers responded to the questionnaire. The average age was 34.5 (±10.94SD), 74.6% were male. The average work experience was 11.8 years (±9.7), 21.4% were medical doctors. Experience with a call of a life-threatening emergency involving a child was reported by 61.5% and severe psychological distress during such a call was reported by 60.4%. The equivalent distress frequency for adult patient calls was 38.3%. (p < 0.001). After review of the case report, the EMS respondents suggested invasive treatment options and rapid transport to the hospital. Most (93.7%) respondents welcomed the consideration of special training in pediatric palliative care. This training should include basic information about palliative care, an analysis of cases involving palliatively treated children, an ethical perspective, practical recommendations, and available (24/7) local contact for further guidance and support. Conclusion: Emergencies in pediatric palliatively treated patients were more common than expected. EMS providers perceived the situations as stressful, and there is a need for specific training with practical aspects.